Kecerdasan Emosi Siswa terhadap Motivasi Belajar Siswa di Masa Pandemi Covid-19 SMP Jakarta Timur - Nurkaidah Nurkaidah; Farida Susantina (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2022)
The research aims to (1) describe emotional intelligence on the learning motivation of East Jakarta junior high school students during the Covid-19 pandemic, (2) analyze the effect of emotional intelligence on learning motivation of East Jakarta junior high school students during the Covid-19 pandemic. Using quantitative, with associative types. The sample is 100 junior high school students in Jakarta. The results of simple linear regression analysis, obtained the equation that learning motivation: 26,151 + 0,755 emotional intelligence. The constant value of learning motivation is 26,151, while the regression coefficient for emotional intelligence is 0.755. The constant value is positive, meaning that if there is no emotional intelligence, the learning motivation is 26,151. The regression coefficient is positive, meaning that there is a positive relationship between emotional intelligence variables and learning motivation. If emotional intelligence has increased by 1% then students' learning motivation will increase by 75.5%. Based on the results of the t test, obtained a significance value: 0.000 and t count: 14,404. Significance value: 0.000 less than 0.05, meaning that there is a significant influence between the independent variable of emotional intelligence on the dependent variable of learning motivation of East Jakarta Middle School students during the Covid-19 pandemic.. Research on the analysis of students' emotional intelligence on student learning motivation during the covid-19 pandemic is expected to find out new information about the factors of students' emotional intelligence problems during online learning so that it can increase students' online learning motivation. The method used is purposive random sampling, the use of questionnaires and descriptive analysis through statistical tests Keywords: Emotional Intelligence; Motivation to learn; Covid-19 pandemic